THE HUMAN RESOURCE PRACTICES IN EMPLOYEE PERFORMANCE: A SIGNIFICANT MANAGERIAL ISSUE - Latupeirissa, Jonathan Jacob Paul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Professional Human Resource Management is needed starting from planning to achieving implementation to improve employee performance. The purpose of this study was to determine the extent of the influence of Emotional Quotient, individual characteristics, and communication on performance and to determine which of the three variables had the most significant effect. This research was conducted at the Tourism Office of Badung Regency, Bali Province, using quantitative methods. The sampling technique used is saturated sampling or census, in which all members of the population are used as samples with a total of 108 respondents. The data analysis technique used is multiple linear regression analysis using the smart PLS program. The results of the research show that each variable, namely Emotional Quotient, Individual Characteristics, and Communication has a positive and significant influence on employee performance. This study also indicates that Communication has the highest influence value with a path coefficient value of 0.462. The coefficient of determination (R2) of = 0.766 can be interpreted that the variables of Emotional Quotient, Individual Characteristics, and communication in influencing employee performance are 76.6%. The remaining 23.4% is explained by other variables not described in the model.